Structural and functional analysis of a conjugated bile salt hydrolase from Bifidobacterium longum reveals an evolutionary relationship with penicillin V acylase - Kumar, R. Suresh; Brannigan, James A.; Prabhune, Asmita; Pundle, Archana V.; Dodson, Guy G.; Dodson, Eleanor J.; Suresh, C. G. (Journal of Biological Chemistry, 2006)
Bile salt hydrolase (BSH) is an enzyme produced by the intestinal microflora that catalyzes the deconjugation of glycine- or taurine-linked bile salts. The crystal structure of BSH reported here from Bifidobacterium longum reveals that it is a member of N-terminal nucleophil hydrolase structural superfamily possessing the characteristic alpha beta beta alpha tetra-lamellar tertiary structure arrangement. Site-directed mutagenesis of the catalytic nucleophil residue, however, shows that it has no role in zymogen processing into its corresponding active form. Substrate specificity was studied using Michaelis-Menten and inhibition kinetics and fluorescence spectroscopy. These data were compared with the specificity profile of BSH from Clostridium perfrigens and pencillin V acylase from Bacillus sphaericus, for both of which the three-dimensional structures are available. Comparative analysis shows a gradation in activity toward common substrates, throwing light on a possible common route toward the evolution of pencillin V acylase and BSH.

Structural modelling of substrate binding and inhibition in penicillin V acylase from pectobacterium atrosepticum - Avinash, Vellore Sunder; Panigrahi, Priyabrata; Suresh, C. G.; Pundle, Archana V.; Ramasamy, Sureshkumar (Biochemical and Biophysical Research Communications, 2013)
Penicillin V acylases (PVAs) and bile salt hydrolases (BSHs) have considerable sequence and structural similarity; however, they vary significantly in their substrate specificity. We have identified a PVA from a Gram-negative organism, Pectobacterium atrosepticum (PaPVA) that turned out to be a remote homolog of the PVAs and BSHs reported earlier. Even though the active site residues were conserved in PaPVA it showed high specificity towards penV and interestingly the penV acylase activity was inhibited by bile salts. Comparative modelling and docking studies were carried out to understand the structural differences of the binding site that confer this characteristic property. We show that PaPVA exhibits significant differences in structure, which are in contrast to those of known PVAs and such enzymes from Gram-negative bacteria require further investigation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bile salt hydrolase; docking; Homology modelling; Inhibition; Pectobacterium; Penicillin acylase